Breeding biology and natural history of the slate-throated whitestart in Venezuela - Ruggera, Román Alberto (2010)
We provide details on the breeding biology of the Slate-throated Whitestart (Myioborus miniatus) from 126 nests found during seven breeding seasons, 2002-2008, at Yacambú National Park, Venezuela. Nesting activity peaked in late April and May. Only the female built the nest and incubated the eggs. Males rarely visited the nest during these stages. Mean clutch size (2.1 ± 0.04 eggs, n = 93) was the smallest recorded for the Slate-throated Whitestart. Incubation and nestling period lengths were 15.3 ± 0.31 (n = 21) and 10.8 ± 0.24 (n = 7) days, respectively. Attentiveness (% of time on the nest) during incubation (59 ± 1.6%, n = 52) was similar to other tropical warblers and much lower than northern relatives. This caused a relatively low egg temperature (34.40 ± 0.33° C, n = 6 nests, 20 days) compared with north temperate birds. Both parents fed nestlings and increased their provisioning rates with nestling age. Growth rate based on nestling mass (k = 0.521 ± 0.015) was faster than for other tropical passerines but slower than northern relatives. Predation was the main cause of nesting failure and rate of predation increased with age of the nest. An estimated 15% of nests were successful based on an overall Mayfield daily predation rate of 0.053 ± 0.007. This study confirms a strong latitudinal variation in life history traits of warblers.